E-Cigarettes: Implications for Health Promotion in the Asian Pacific Region. (May 2018) - Jancey, Jonine; Maycock, Bruce; McCausland, Kahlia; Howat, Peter
Since their introduction to the United States in 2007, electronic cigarettes (e-cigarettes) use has grown exponentially. This rapid growth in e-cigarette use has been heralded by some as a potential important public health measure that could ultimately replace tobacco cigarettes, while others recommend a cautionary approach until there is clear evidence they will not become "new tobacco" bringing a possible myriad of other problems. E-cigarettes may have real benefits, however they do expose users and those nearby to organic compounds, solvents and particulate matter, with there being limited data relating to their health impact. It is unclear as to whether this relatively new device has the potential to exacerbate nicotine addictions, or play a part in reducing harm and smoking cessation. The fundamental requirement of public health practice is to do no harm and from the inconclusive evidence we have to date on e-cigarettes, it appears a cautious approach is warranted. This commentary reviews evidence that supports a cautious approach to e-cigarette availability in Australia and the Asian Pacific region.